2021
DOI: 10.1002/cam4.3978
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid dysfunction and breast cancer risk among women in the UK Biobank cohort

Abstract: This study aimed to evaluate the association between thyroid dysfunction and breast cancer risk. We included 239,436 females of the UK Biobank cohort. Information on thyroid dysfunction, personal and family medical history, medications, reproductive factors, lifestyle, and socioeconomic characteristics was retrieved from baseline self‐reported data and hospital inpatient databases. Breast cancer diagnoses were identified through population‐based registries. We computed Cox models to estimate hazard ratios (HRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…UK cancer has an opportunity to deploy its unique integrated data intelligence platforms to address many of issues above. These systems of data capture and linkage enable formulation of datasets that include information on every cancer diagnosis, all hospital episodes and procedures, information on radiotherapy, surgery and SACT 114 as well as the opportunity to integrate genetic testing data, GP records and patient reported outcome measures [115][116][117][118][119] .…”
Section: Services and Systemsmentioning
confidence: 99%
“…UK cancer has an opportunity to deploy its unique integrated data intelligence platforms to address many of issues above. These systems of data capture and linkage enable formulation of datasets that include information on every cancer diagnosis, all hospital episodes and procedures, information on radiotherapy, surgery and SACT 114 as well as the opportunity to integrate genetic testing data, GP records and patient reported outcome measures [115][116][117][118][119] .…”
Section: Services and Systemsmentioning
confidence: 99%
“…Initial investigations found that patients with hypothyroidism had higher risk of breast cancer [ 23 , 24 ]. However, other studies showed that hypothyroidism was associated with a reduced risk of this tumor [ 21 , 25 ] or that there was no significant relationship [ 13 , 17 , 26 31 ]. A meta-analysis including 12 studies showed that there was a 6% increase in risk for breast cancer among women with primary hypothyroidism [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initial investigations found that patients with hypothyroidism had higher risk of breast cancer [23,24]. However, other studies showed that hypothyroidism was associated with a reduced risk of this tumor [21,25] or that there was no significant relationship [13,17,[26][27][28][29][30][31].…”
Section: Plos Onementioning
confidence: 99%
“…Кроме того, обнаружено, что тироксин -фактор пролиферации клеток РМЖ in vitro и что тироксин может стимулировать альфа-зависимую от ядерного рецептора эстрогена пролиферацию клеток РМЖ, несущих этот рецептор [38]. Однако по данным одного из исследований риск РМЖ варьировал в зависимости от статуса лечения гипертиреоза, при этом риск РМЖ у женщин, получавших лечение от гипертиреоза, был на 38% выше по сравнению с таковым у женщин без дисфункции щитовидной железы [39]. Среди женщин в постменопаузе связь между Т 4 и риском развития РМЖ также была сильнее у женщин с ожирением, у которых концентрация эстрогена в крови была выше, чем у женщин с нормальным весом [40].…”
Section: рак щитовидной железыunclassified